High Glucose Enhances Cytotoxic T Lymphocyte-Mediated Cytotoxicity - Zhu, Jie; Yang, Wenjuan; Zhou, Xiangda; Zöphel, Dorina; Soriano-Baguet, Leticia; Dolgener, Denise; Carlein, Christopher; Hof, Chantal; Zhao, Renping; Ye, Shandong; Schwarz, Eva C.; Brenner, Dirk; et al. (Frontiers in Immunology, 2021)
Cytotoxic T lymphocytes (CTLs) are key players to eliminate tumorigenic or pathogen-infected cells using lytic granules (LG) and Fas ligand (FasL) pathways. Depletion of glucose leads to severely impaired cytotoxic function of CTLs. However, the impact of excessive glucose on CTL functions still remains largely unknown. Here we used primary human CD8+ T cells, which were stimulated by CD3/CD28 beads and cultured in medium either containing high glucose (HG, 25 mM) or normal glucose (NG, 5.6 mM). We found that in HG-CTLs, glucose uptake and glycolysis were enhanced, whereas proliferation remained unaltered. Furthermore, CTLs cultured in HG exhibited an enhanced CTL killing efficiency compared to their counterparts in NG. Unexpectedly, expression of cytotoxic proteins (perforin, granzyme A, granzyme B and FasL), LG release, cytokine/cytotoxic protein release and CTL migration remained unchanged in HG-cultured CTLs. Interestingly, additional extracellular Ca2+ diminished HG-enhanced CTL killing function. Our findings suggest that in an environment with excessive glucose, CTLs could eliminate target cells more efficiently, at least for a certain period of time, in a Ca2+-dependent manner.